2020
DOI: 10.1182/bloodadvances.2020002098
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of CD4+ T cells in PD-1 blockade against MHC-II–expressing tumors such as classic Hodgkin lymphoma

Abstract: Classic Hodgkin lymphoma (cHL) responds markedly to PD-1 blockade therapy, and the clinical responses are reportedly dependent on expression of major histocompatibility complex class II (MHC-II). This dependence is different from other solid tumors, in which the MHC class I (MHC-I)/CD8+ T-cell axis plays a critical role. In this study, we investigated the role of the MHC-II/CD4+ T-cell axis in the antitumor effect of PD-1 blockade on cHL. In cHL, MHC-I expression was frequently lost, but MHC-II expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 58 publications
3
76
0
Order By: Relevance
“…In addition, it is not clear yet whether CD4 memory T cells could also play a role within the tumor microenvironment under PD-L1/PD-1 blockade therapy. A recent study in Classic Hodgkin lymphoma (CHL) murine models demonstrated that PD-1 blockade therapy has strong anti-tumor effects on MHC-II expressing tumors mediated by cytotoxic CD4+ T cells (77). Moreover, they observed that CHL patients responding to PD-1 blockade therapy exhibited high CD4+ T cell infiltration compared to non-responders (77).…”
Section: Cd4 Immunity Has An Important Contribution To Pd-l1/pd-1 Blomentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is not clear yet whether CD4 memory T cells could also play a role within the tumor microenvironment under PD-L1/PD-1 blockade therapy. A recent study in Classic Hodgkin lymphoma (CHL) murine models demonstrated that PD-1 blockade therapy has strong anti-tumor effects on MHC-II expressing tumors mediated by cytotoxic CD4+ T cells (77). Moreover, they observed that CHL patients responding to PD-1 blockade therapy exhibited high CD4+ T cell infiltration compared to non-responders (77).…”
Section: Cd4 Immunity Has An Important Contribution To Pd-l1/pd-1 Blomentioning
confidence: 99%
“…A recent study in Classic Hodgkin lymphoma (CHL) murine models demonstrated that PD-1 blockade therapy has strong anti-tumor effects on MHC-II expressing tumors mediated by cytotoxic CD4+ T cells (77). Moreover, they observed that CHL patients responding to PD-1 blockade therapy exhibited high CD4+ T cell infiltration compared to non-responders (77). Another study using murine models demonstrated that the expansion of tumor infiltrating follicular CD4+ PD1+ T cells after PD-1 blockade therapy correlated with enhanced CD8 CTL anti-tumor responses and tumor growth control (78).…”
Section: Cd4 Immunity Has An Important Contribution To Pd-l1/pd-1 Blomentioning
confidence: 99%
“…Indeed, studies on murine solid tumor models revealed that PD-1 blockade exerted anticancer effects against MHC-I − MHC-II + but not MHC-I − MHC-II − tumors. In addition, the anticancer activity of anti-PD-1 antibodies was abolished in mice depleted of CD4 + T-cells, but not CD8 + T-cells [ 86 ]. Independent studies have also shown that Th lymphocytes may mount a cytolytic response in appropriate contexts [ 86 , 87 ].…”
Section: How Hrs T and Nk Cells Predict Response To Pd-1 Blockadementioning
confidence: 99%
“…In addition, the anticancer activity of anti-PD-1 antibodies was abolished in mice depleted of CD4 + T-cells, but not CD8 + T-cells [ 86 ]. Independent studies have also shown that Th lymphocytes may mount a cytolytic response in appropriate contexts [ 86 , 87 ]. Mice bearing MHC-II + tumors had larger amounts of intratumoral CD4 + T-cells that stained positive for GrB, and this subset further increased following PD-1 blockade [ 86 ].…”
Section: How Hrs T and Nk Cells Predict Response To Pd-1 Blockadementioning
confidence: 99%
See 1 more Smart Citation